IbM Pelatihan, Pembinaan dan Pendampingan Penggunaan Aplikasi Management Stock Control - Wali, Muhammad; Ismail; Iqbal, Taufiq; Syafwandhinata, Jhony (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this service activity is to provide Training, Coaching, and Assistance for Stock Control Management Applications and it is hoped that the participants can; 1) Understand the strategy for the supply of goods, 2) Understand and be able to control spare parts, 3) Be able to provide the goods needed in the remodeling process, 4) Be able to manage spare parts efficiently and be able to apply methods Determine the level of reordering and minimum inventory for inventory optimization, and 5) Evaluating the material planning system that has been running so that we can find out the core of the problems faced and how to solve them. The method of implementing the program to be carried out is; 1) Presentation, 2) Experience Sharing Discussion, 3) Training (Training for Users), and 4) Further assistance in the use of the application. This Community Service Implementation Activity was held for 4 (four) months from early December 2019 to the end of March 2020. This activity was attended by all personnel of Gober Indo's local business partners. Based on the results of the activities that have been carried out, several conclusions can be drawn, namely; 1) The development of a web-based Stock Control Management application has been successfully built, 2) Assistance and training activities for the use of the appropriate Stock Control Management Application and can help partners, 3) Service activities that are followed very enthusiastically, It can be seen that many members and owners have attended the training, and 4) Supporting activities for the Stock Control Management Application are expected to continue with the development of partner business finances.